Indian castor oil exports concentration- a perspective: Indian castor oil exports concentration- a perspective - N SANDRA,; C SARADA,; N K CHAURE, (Journal of Oilseeds Research, 2020)
India is the global leader and ranks first in production with almost 87 percent of world’s share as well as inexports of castor oil with a share of 86.8 percent of world’strade (2018-19) and the export is valued at ` 5658 crores. Geographic concentration was analyzed using Herfindahl-Hirschman Index (HHI). It showed that the exports are highly concentrated ranging from 2032 to 2584 for the last eight years except for the year 2014-15 when it was 1668 (moderate concentration).The analysisrevealed thatthe castor oil export destinations are highlyconcentrated to only 10 countries. However, diversification of markets is always desirable